Postphagocytic detection of glycopeptidolipids associated with the superficial L1 layer of Mycobacterium intracellulare. - Tereletsky, M J (1983)
The superficial L1 layer of Mycobacterium intracellulare serovar 20 was detected by immunocytochemical procedures based on C-mycoside glycopeptidolipid (GPL) antigens. Specific immune serum was produced by injecting a GPL-methylated bovine serum albumin complex into rabbits with Freund incomplete adjuvant. The resulting antibodies were used to label serovar 20 with goat anti-rabbit immunoglobulin G (IgG) conjugated with either fluorescein or ferritin. The labeled GPL antigens were then detected by fluorescent and electron microscopy. With these procedures, it was possible to observe the superficial distribution of the GPL antigens on serovar 20 and to confirm their intraphagosomal location within the macrophages after phagocytosis. These immunocytochemical procedures now make it possible to monitor these mycobacterial antigens during phagocytosis and may be helpful in determining their role in pathogenesis.